ANALISIS PERSEDIAAN TEPUNG BERAS ROSE BRAND PADA PT. SUNGAI BUDI DI SAMARINDA - Rina Masithoh Haryadi3, Nurlinawati Elfreda Aplonia Lau (EKONOMIA, 2021)
ABSTRACTInventory is always needed by every company, both small and large companies. With the inventory procurement policy, it is hoped that the sales process can run smoothly. Without an inventory of merchandise, the company is faced with the risk that one day the company will not be able to meet consumer needs.This study aims to determine and analyze whether the supply of rice flour is optimal and the efficiency or not the cost of rice flour supplies at PT Sungai Budi Samarinda by raising the following problems:1. Has the control of 20 bks / dus @ 500gr rice flour supply at PT Sungai Budi been carried out efficiently? 2. Is the procurement of rice flour 20 bks / dus @ 500gr PT Sungai Budi carried out optimally?The theoretical basis used is management accounting which focuses on inventory control and inventory cost efficiency of rice flour.The research hypothesis is:1. There is an efficiency in inventory costs after using the EOQ method2. Determination of rose brand rice flour inventory by the EOQ method can overcome the shortage / excess inventory.The analytical tool used is EOQ (Economics Order Quantity), Determining Total Inventory Costs, (Safety Stock), (Reorder Points)The results showed that:1. There was an efficiency of inventory costs amounting to Rp 893,276,3792. The use of the EOQ method can help companies in determining the optimal inventory or which minimizes inventory costs.